Slavic verb aspect: A step too high for native-like speakers competence - Jelaska, Zrinka; Cvikić, Lidija; Musulin, Maša (2005)
Verb aspect, e.g. difference between perfective and imperfective verbs (or verb forms) is considered to be the most complex phenomenon in acquiring Slavic languages by L2 learners. Although other types of languages express or may express the same meaning by other linguistic means that is contained within Slavic verb forms, the factors affecting verb form choices in Slavic seem to be complex as they come from various kinds of linguistic levels: syntactic, semantic, pragmatic, stylistic... This paper deals with written production and recognition of verbal aspect in Croatian by the learners of Croatian as L2. On the basis of pre-testing and post-testing at various language tasks it will be showed how a four weeks intensive course affects the learner's awareness of correct usage of the verbal aspects. The results will also be compared with the usage of verbal aspect in learner's free compositions according to the accuracy and degree of communicative acceptance.
Projekt MZOS
ENG